A Review of Liquid and Gaseous Biofuels from Advanced Microbial Fermentation Processes - Sonil Nanda; Falguni Pattnaik; Biswa R. Patra; Kang Kang; Ajay K. Dalai (Fermentation, 2023)
Biofuels are the sustainable counterparts of fossil fuels to meet the increasing energy demands of the current and future generations. Biofuels are produced from waste organic residues with the application of mechanical, thermochemical and biological methods and processes. While mechanical and thermochemical conversion processes involve the use of heat, pressure, catalysts and other physicochemical attributes for the direct conversion of biomass, biological conversion requires microorganisms and their enzymes as biocatalysts to degrade the fermentable substrates into biofuels and biochemicals. This article highlights the advances and opportunities in biological conversion technologies for the development of a closed-loop biorefinery approach. This review highlights the distinction between biological and thermochemical conversion technologies, including a discussion on the pros and cons of the pathways. Different categories of biological conversion processes, such as enzymatic saccharification, submerged fermentation, solid-state fermentation and simultaneous saccharification and fermentation are also discussed in this article. The main essence of this article is the description of different fermentative technologies to produce next-generation biofuels, such as bioethanol, biobutanol, biomethane, biohydrogen and biodiesel. This article provides a state-of-the-art review of the literature and a technical perspective on the bioproduction of bioethanol, acetone–ethanol–butanol fermentation, anaerobic digestion, photo/dark fermentation, and the transesterification of lignocellulosic substrates to produce the above-mentioned biofuels. In addition, recommendations for improving bioprocessing efficiency and biofuel yields are provided in this comprehensive article.